2007
DOI: 10.1200/jco.2006.09.7915
|View full text |Cite
|
Sign up to set email alerts
|

Customizing Cisplatin Based on Quantitative Excision Repair Cross-Complementing 1 mRNA Expression: A Phase III Trial in Non–Small-Cell Lung Cancer

Abstract: Assessment of ERCC1 mRNA expression in patient tumor tissue is feasible in the clinical setting and predicts response to docetaxel and cisplatin. Additional studies are warranted to optimize methodologies for ERCC1 analysis in small tumor samples and to refine a multibiomarker profile predictive of patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
264
2
17

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(293 citation statements)
references
References 25 publications
8
264
2
17
Order By: Relevance
“…Other studies showed that the low intratumoral ERCC1 mRNA expression was associated with favorable clinical outcomes after treatment with platinum-based chemotherapy in lung cancer [27,28] , colorectal cancer [29] , gastric cancer [30][31][32] , ovarian cancer [33] , bladder cancer [34] , head and neck cancer [35] . A recent phase Ⅲ trial in nonsmall-cell lung cancer also demonstrated that assessment of intratumoral ERCC1 mRNA expression is feasible in the clinical setting and predicts response to cisplatin [36] . However, most of those studies focused on the influence of ERCC1 expression on the effect of platinum-drug in advanced or metastatic diseases, little was known about its effect on platinum-drug adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that the low intratumoral ERCC1 mRNA expression was associated with favorable clinical outcomes after treatment with platinum-based chemotherapy in lung cancer [27,28] , colorectal cancer [29] , gastric cancer [30][31][32] , ovarian cancer [33] , bladder cancer [34] , head and neck cancer [35] . A recent phase Ⅲ trial in nonsmall-cell lung cancer also demonstrated that assessment of intratumoral ERCC1 mRNA expression is feasible in the clinical setting and predicts response to cisplatin [36] . However, most of those studies focused on the influence of ERCC1 expression on the effect of platinum-drug in advanced or metastatic diseases, little was known about its effect on platinum-drug adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis on mRNA expression results of ERCC1 gene demonstrated that 40.00% pertained to low expression in postoperative patients with NSCLC, suggesting that 40.00% of patients with NSCLC are sensitive to platinum chemotherapy, but the resistance to drugs is not dependent on the expression level of one gene or protein at all (Cobo et al, 2007). On the other hand, the detection of expression quantity to this gene can preliminarily screen out a part of patients with drug resistance so as to guide clinical administration better.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 In the only prospective randomized clinical trial testing customized chemotherapy in advanced NSCLC, ERCC1 mRNA predicted for response to cisplatin-based chemotherapy in 346 patients. 47 Some researchers have demonstrated that in earlystage NSCLC surgically resected for cure, ERCC1 expression was also prognostic in favor of longer survival. [48][49][50] However, the finding was not confirmed in all studies.…”
Section: Discussionmentioning
confidence: 99%